197k views
4 votes
−3x − 3y = 3

y = −5x − 17

Solve the above system of equations using substitution. Show all work.

Please help. I have the flu and my brain isn't working.

1 Answer

3 votes

Answer:

(x, y) = (-4, 3)

Explanation:

I would start by dividing the first equation by 3 (because you can).

-x -y = 1

Now, substitute the expression in the second equation for y:

-x -(-5x -17) = 1

-x +5x +17 = 1 . . . . . use the distributive property to eliminate parentheses

4x = -16 . . . . . . . . . . collect terms, subtract 17

x = -4 . . . . . . . . . . . . divide by 4

y = -5(-4) -17 = 20 -17 = 3 . . . . . substitute for x in the second equation

The solution is (x, y) = (-4, 3).

User Dhruv Chandhok
by
5.1k points